The Juridical Analysis of Criminal Responsibility Performer on Children - Aris Munandar Pamungkas; Umar Ma'ruf; Bambang Tri Bawono (Universitas Islam Sultan Agung, 2022)
The purpose of this study was to identify and analyze the factors that influence the occurrence of criminal acts of sexual abuse against children. To find out and analyze the criminal responsibility of perpetrators of sexual abuse against children. The method used by the researcher is empirical juridical approach and the specifications in this study were descriptive. The sources of data in this study were secondary data obtained from literature studies and the processing of the researched data was then analyzed qualitatively, namely the analysis of the data to produce data that was systematically arranged based on the laws and regulations, the opinions of experts and the results of the author's research. Based on the results of the study that Factors Affecting the Occurrence of the Crime of Child Abuse as follows: Environmental Factors, Cultural Factors, Economic Factors and Educational Factors.Criminal Liability of Perpetrators of Obscenity Against Children is prosecute perpetrators with criminal sanctions for perpetrators of sexual abuse of children according to the Criminal Code (KUHP), namely article 289. And with criminal sanctions for perpetrators of sexual abuse of minors according to Act No. 23 of 2002 concerning Child Protection, namely article 82.